Effect of Bioaugmentation by Bacterial Consortium and Methyl-β-cyclodextrin on Soil Functional Diversity and Removal of Polycyclic Aromatic Hydrocarbons. (8th August 2019) - Tian, Fang; Guo, Guang; Ding, Keqiang; Wang, Lihong; Liu, Tingfeng; Yang, Feng
ABSTRACT: The low biological effectiveness of polycyclic aromatic hydrocarbons (PAHs) is the main limiting factor of in-situ bioremediation of PAH-contaminated soil. The purpose of the present study was to assess the effects of methyl-β-cyclodextrin (MCD) and microbial consortia on the PAHs degradation rate and microbial ecology and functional diversity and stability in soil. The results show that MCD and microorganisms significantly increased the degradation rate of pyrene and benzo[a]pyrene by 30.1% and 9.1%, respectively, ( p < 0.05) after 4 weeks. The average well color development (AWCD) values and diversity indices of bioaugmentation (B) and MCD- and bacterial-assisted bioaugmentation (MB) were significantly higher than that in control (CK). The Shannon–Weaver index (H) and McIntosh index (U) in the MB treatment were significantly higher than those observed in other treatments, which indicated that its species richness and individuals were distributed evenly. The soil microbial activity and community structure were the most abundant in the MB treatment. Compared to the CK treatment, MB significantly promoted soil dehydrogenase activity (DHA) and fluorescein diacetate hydrolysis (FDAH) enzyme activity, which were increased by 96.3% and 994.3%, respectively. According to the results of principal component analysis, the physiological functions of microbial communities in the MB and B treatments were different from the other treatments. Therefore, the combination of the microorganisms with MCD can stimulate the remediation efficiency of PAHs and the physiological functions of microbial communities.